Identification of The Basic Sector and The Regional Budget in Promoting The Economy of Nganjuk District - Ermita Yusida; Firman Maulana (MediaTrend, 2022)
The purpose of this study is to identify the basic sector in Nganjuk Regency alongwith the proportion of the budget allocated by the local government through theRegional Budget (APBD) for the 2017 budget year. The method used in determining the sector base is Location Quotient (LQ) which is then developed in the dynamic location quotient. (DLQ). The data used in the research are the 2016 Gross RegionalDomestic Product (PDRB) of Nganjuk Regency, 2016 East Java GRDP, and the 2017Nganjuk Regency APBD. The results of the DLQ calculations state that there are12 basic sectors in Nganjuk Regency. However, some of these basic sectors have notreceived a large proportion of the budget to develop. In the future, the governmentand related stakeholders can determine the correct proportion of the APBD tosupport the basic sector development.